2018
DOI: 10.1002/cjce.23286
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of the surface reactivity of 2D α‐Mo2C crystallites

Abstract: A preliminary study of the surface reactivity of 2D‐α‐Mo2C crystallites grown on a copper foil was performed using x‐ray photoelectron spectroscopy. Different sample preparation protocols for the as‐received materials were explored in order to remove hydrocarbon surface contamination. Annealing in vacuum and in argon led to the formation of graphitic layers, while annealing in O2 lead to almost the complete disappearance of the Mo signal. Gentle argon ion sputtering proved effective at removing the hydrocarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…By comparing the XPS pattern data on furfural on prepared molybdenum carbide with the results of previous studies of ketones and aldehydes on β‐Mo 2 C, Fortin et al. concluded that the similar results demonstrate the rich surface sp 2 and sp 3 carbon of molybdenum carbide crystals, which is crucial for thermal de/hydrogenation catalytic processes [41] …”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…By comparing the XPS pattern data on furfural on prepared molybdenum carbide with the results of previous studies of ketones and aldehydes on β‐Mo 2 C, Fortin et al. concluded that the similar results demonstrate the rich surface sp 2 and sp 3 carbon of molybdenum carbide crystals, which is crucial for thermal de/hydrogenation catalytic processes [41] …”
Section: Introductionmentioning
confidence: 71%
“…[40] By comparing the XPS pattern data on furfural on prepared molybdenum carbide with the results of previous studies of ketones and aldehydes on β-Mo 2 C, Fortin et al concluded that the similar results demonstrate the rich surface sp 2 and sp 3 carbon of molybdenum carbide crystals, which is crucial for thermal de/hydrogenation catalytic processes. [41] In recent years, researchers have achieved more advances in improving the performance of molybdenum carbide-based catalysts as numerous innovative catalyst manufacturing techniques and characterization tools have been brought into the study of molybdenum carbide. Doping engineering, [34,42,43] morphology and structure engineering, [44][45][46] carrier engineering, [47][48][49] and encapsulating engineering, [50,51] which have been demonstrated to increase the microscopic electronic structure and crystal stability of catalysts, have also been utilized to improve the de/hydrogenation catalytic activity of molybdenum carbide.…”
Section: Introductionmentioning
confidence: 99%
“…The special section consists of sixteen accepted articles that were organized in four topics. The first gathers contributions on industrially important catalysis applications and energy conversion (Fischer‐Tropsch synthesis, molybdenum carbide catalysis, coal pyrolysis and gasification, biorefinery transformations, carbon dioxide biomass gasification, and baffled fluidized and bubble column reactors). The second topic picked up a couple of biotechnology applications (enzyme immobilization on magnetic nanoparticles and cell adhesion on collagen scaffolds).…”
mentioning
confidence: 99%